Consensus views on the optimum training curriculum for advanced minimally invasive surgery: A delphi study. (May 2018) - Awad, Mina; Awad, Fady; Carter, Fiona; Jervis, Bethan; Buzink, Sonja; Foster, Jake; Jakimowicz, Jack; Francis, Nader K.
Abstract: Introduction: There has been a wide uptake in the use of Minimal Invasive Surgery (MIS) globally across different surgical specialties. Whilst evidence exists for a structured training curriculum for basic laparoscopic surgery, there is little agreement on a complete framework for an advanced MIS training curriculum, defining the essential elements of the curriculum including the optimal assessment methods. The aim of this study is to obtain a consensus on the essential elements of a training curriculum for advanced MIS. Materials and Methods: A Delphi study was carried out involving 57 international experts in advanced MIS across different surgical specialties. A three round survey was conducted to reach consensus on the essential domains of a curriculum. This included defining the learners, trainers and training centres; curriculum content and competency based assessment. Results: Unanimous agreement was reached for the completion of basic laparoscopic training before entry into advanced training. A trainer should have reached competency in advanced MIS and attended a 'Train the trainer' course. The curriculum should be delivered as modular training, including a multi-modal approach with a structured clinical proctorship programme. Formative assessment was considered as an integral part of learning and should be performed using objective work based assessment tools such as global assessment scale (GAS) forms. Accreditation in advanced MIS can be achieved by objective assessment of technical performance of unedited videos in addition to key clinical performance outcomes. Conclusion: A consensus on the framework of an advanced MIS training curriculum has been achieved defining the essential elements of entry criteria, selection of trainers and training units and curriculum content. Multimodal learning, clinical proctorship programme and competency based assessment are integral parts of the curriculum. Highlights: A curriculum for advanced minimal invasive surgery has been developed. This was achieved through an international consensus process. Curriculum outlines selection of trainees, trainers, training units and assessment.